Efeitos da infusão profilática contínua de fenilefrina sobre a estratégia de redução da massa de anestésico local em pacientes submetidas à raquianestesia para cesariana - Souza, Vinícius Pereira de [UNIFESP] (2010)
Background: Reduced local anesthetic dose is used for minimizing hypotension changes related with spinal anesthesia for cesarean section, optimizing both maternal and fetal outcomes. This strategy can result in neuroaxial block failure. On the other hand, the higher doses associated with hypotension can be controlled with continuous prophylactic infusion of phenylephrine. The present study assessed the effects of continuous infusion of phenylephrine under strict blood pressure control and the maternal-fetal outcomes in patients under spinal anesthesia for elective cesarean section with two anesthetic solution. Methods: The number of 60 patients, scheduled for elective cesarean section, was allocated into 2 non-randomized groups (30 individuals each) for this prospective clinical study identified as Group 12 (G12), who were administered 12 mg hyperbaric bupivacaine and; Group 8 (G8), who were injected with 8 mg hyperbaric bupivacaine. In both groups, the anesthetic solution was added to sufentanyl 5 !g and morphine 100 !g. Pre-hydration with Ringer Lactate solution – 10 ml/Kg. Continuous phenylephrine infusion started at the end of the spinal block, with a infusion rate of 100 !g/min under strict blood pressure control. Comparatively, sensitive anesthetic block level, vasopressor consumption, adverse maternal and neonate outcomes were evaluated. Results: The incidence of maternal adverse effects such as nausea, vomiting, dispnea, pain, tremor, and bradicardy, necessity of atropine, hypotension and hypertension showed no significant difference between groups. In addition, other parameters were evaluated in neonates, pH, pCO2, BE and lactate of umbilical vases and the consumption of phenylephrine per time unit. All neonates showed pH higher than 7.20, as well as the Apgar score higher than 7 at 5`; only one neonate of G12 showed the Apgar score lower than 7 at 1`. Conclusion: Strict arterial blood pressure performed with prophylactic continuous infusion of phenylephrine, doesn’t change the maternal and fetal outcomes in patients scheduled for elective cesarean section under spinal anesthesia.